ONLINE ORGAN DONATION MANAGEMENT SYSTEM (International Journal of Food and Nutritional Sciences, 2024)
The Organ Donation System seeks to facilitate organ donation and organ delivery to individuals in need. Our major purpose is to address the issue of insufficient organs accessible for transplantation.Our system makes it simple for people who wish to donate their organs to sign up and connects them with organ recipients.We use technology to smooth out and open up the processes.We want to save more lives by raising awareness and streamlining the donation process.Transparency in the collection and distribution of gifts is facilitated by the system's tracking of donor information from throughout the nation.Additionally, it handles user information and donation sign-ups, giving consumers a means to get engaged. Organ donation is essential for providing patients with organ failure with a second shot at life.